Transient Raman snapshots of the twisted intramolecular charge transfer state - Dasgupta, Jyotishman (2020)
Optically triggered twisted intramolecular charge transfer (TICT) states in donor-acceptor chromophores form the molecular basis for designing bio-imaging probes that sense polarity, microviscosity or pH in vivo.[1] However, a lack of predictive understanding of the ‘twist’ localization has limited rational structure-function correlations for TICT-based dyes. Time-resolved absorption and emission spectroscopy traditionally used to address this problem, could never unequivoally identify the twist location.[2] Here, using femtosecond stimulated Raman spectroscopy, we reveal distinct Raman signature of the TICT state for stilbazolium-class of mitochondrial staining dye for the first time.